L’engouement des communautés indigènes équatoriennes pour le tourisme, choix pertinent ou désillusion annoncée ? - Bernard Schéou (Études Caribéennes, 2013)
In September 2007, during a speech to the General Assembly of the United Nations, Ecuadorian president Rafael Correa criticized the vision underlying the Millennium Development Goals (MDGs). Rejecting the strategy of economic liberalization and the increased consumption it implies, Correa stated that his government was in favour of "endogenous development, economic inclusion and social and territorial cohesion" to reduce inequalities and permit a decent standard of life for everyone, adding "our vision of development is very different: we believe in developing the welfare of all, in peace and harmony with nature, and the infinite extension of human cultures."Tourism is one of the largest form of foreign exchange in Ecuador beside oil and remittances from migrants. Can tourism contribute to achieving the goal defined by Correa? How? With more than one million foreign visitors in 2008 (including 24% from the United States and 45% from Latin American countries), international tourism contributed $745 millions to Ecuador’s economy in 2008. Acknowledging tourism as a timely activity, more and more indigenous communities are developing tourism projects. The multinational federation of community-based tourism in Ecuador includes 90 communities, even though all those who set up community tourism projects have not adhered to the federation’s requirements. How can we understand this surge in popularity for tourism from indigenous communities and what are their expectations? Do these projects result in adequate solutions? We will provide some answers through the analysis of two experiments conducted on community-based tourism by Kechua communities in the Andes and the Amazon rainforest.